Water requirement of sugarcane in northwest state of São Paulo - Avilez, Alberto Mario Arroyo [UNESP]; Hernandez, Fernando Braz Tangerino [UNESP]; Bispo, Regiane De Carvalho [UNESP]; Giovanelli, Luan Brioschi (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2018)
The knowledge of the water needs of crops is essential, because in this way, the rational water management can be achieved-increasingly indispensable due to water scarcity. The objective of this work was to estimate the evapotranspiration (ETc) of the sugarcane crop and thus obtain the water need, per crop, in the Northwest region of state of São Paulo. The work was performed out in two commercial farms, in the municipalities of Andradina and Rubineia. In the first farm, total ETc values were estimated for the 2013/2014, 2014/2015, 2015/2016 and 2016/2017 seasons. In the second farm, ETc values were estimated for the 2015/2016 and 2016/2017 seasons. The water needs along of the seasons presented different values for the two farms analyzed, with extreme values of 1095 mm/crop for the commercial farm in Rubineia and 1595 mm/crop for the commercial farm in Andradina. The variation of the water need among the farms occurred due to the crop cycle, the days needed to reach the sugarcane cut-off date, and the reference evapotranspiration (ETo) values. The correct understanding and application of the values of crop coefficient (Kc) and of ETo made it possible to estimate the water need of sugarcane in the northwestern region of state of São Paulo.
Necessidade hídrica da cana-de-açúcar no noroeste paulista
Keywords: Coefficient of crop; Evapotranspiration; Weather data